High thermoelectric performance of TlInSe3 with ultra-low lattice thermal conductivity - Yin, Xixi; Zhou, Lang; Wang, Qi; Liao, Yangfang; Lv, Bing (Frontiers in Physics, 2023)
Thermoelectric (TE) materials with an excellent thermoelectric figure of merit (ZT) provide an effective way to alleviate energy pressure and protect the environment. By applying the first-principles method, this paper makes a systematic study of the electronic and phonon transport properties of two-dimensional (2D) novel TlInSe3 utilizing the Boltzmann transport theory (BTE). The calculation results reveal that 2D TlInSe3 has an excellent power factor (0.81 × 10−2 W/mK2) and ultra-low lattice thermal conductivity (0.46 W/mK) at 300 K. We find that the low phonon group velocity and strong anharmonicity are the main factors leading to the ultra-low lattice thermal conductivity of TlInSe3. Meanwhile, by discussing the acoustic-optical scattering, we attribute low phonon group velocity and strong anharmonicity to the increase of scattering rates between acoustic mode and optical mode, which further suppresses the lattice thermal conductivity. In the analysis of electron and phonon transport properties, 2D TlInSe3, as a novel TE material, exhibits a ZT value as high as 4.15 at 500 K. Our research results show that TlInSe3 is a potential TE material, and the relevant analysis is significant in exploring new TE materials.